Factors influencing sustainable construction in Egypt - Elsamni, Jehan; Hegazy, Hosam; Abdulrasheed, Ibrahim; Kohail, Mohamed (Journal of Civil Engineering and Management, 2026)
The concern about sustainable development has become a global goal, and as such, the United Nations has adopted the seventeen sustainable development goals that are targeted to be achieved by 2030. Furthermore, to address the energy and Greenhouse gases (GHG) crisis, the world has moved towards developing policies concerned with rationalizing energy consumption and reducing GHG emissions. The main idea of sustainable construction is to avoid the depletion of natural resources for both the present and future generations. Therefore, this study aims to investigate the factors that prevent and delay the adoption of sustainable construction practices in Egypt. Using the survey method, a questionnaire was filled out by professionals and practitioners in Egyptian construction projects. The findings of this study indicate that the most critical factors affecting sustainable construction in Egypt are the “poor market demand for green and recyclable construction materials”, and “fear of higher investment costs”. The study recommends raising awareness to overcome these factors.